SYNTAGMATIC LEXICAL RELATIONS IN THE TEXTBOOK "LET'S LEARN SERBIAN 2" (LEXICOLOGICAL ASPECT) - Драгана С. Симеуновић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2015)
Since language is actualized through lexical compounds, this research focused on the rules according to which the relations between lexical compounds are based. Attention was paid to the processing of lexical noun compounds, which were taken from the textbook for learning Serbian as a foreign language "Let's Learn Serbian 2". They were classified with respect to semantic criteria. Depending on whether the elements in a collocation were in a hierarchical relationship or not, primary and secondary collocations were observed. An overview of semantic features was obtained by means of a conceptual analysis and the descriptive method. Following this, the paper put forth the basic structural patterns according to which durable syntagmatic-lexical compounds were formed with respect to the administrative element of a collocation. Some examples of the primary corpus were checked in an electronic corpus to determine a wider range of collocations. After the identification and the presentation of lexical and semantic parameters that governed the resulting lexical compounds, the paper gave an overview of the formal patterns in which the collocation was implemented.